Physico-chemical characterization of essential oils of Rosa indica and its application in hand sanitizer: Rose essential oil as a potential ingredient in hand sanitizer formulation - Javed, Shabnam; Safdar, Asifa; Shoaib, Amna; Nisar, Zahra (International Journal of Biology and Chemistry, 2021)
This research work documents the isolation and physico-chemical characterization of essential oil of Rosa indica L. and its application in hand sanitizer. R. indica essential oil (REO) extracted from freshly collected flower petals through hydro-distillation method showed 0.057% yield. Some of the physico-chemical properties of REO like density (0.92), refractive index (1.45), viscosity (9.46), specific gravity (0.92), optical rotation (optically active), acid number (14.10), ester number (28.19), consistency (solid), appearance (clear liquid), color (pale yellow), odor (floral, sweat rosaceous) and purity (100%) were determined in laboratory using standard protocols. GC-MS analysis of REO identified twenty-nine compounds belong to eight major groups. Monoterpene alcohol represented the main characterized group (59%) followed by sesquiterpenes hydrocarbons (21.20%), phthalate ester (9.99%), aldehyde hydrocarbon (1.41%), alkyne hydrocarbons (1.21%), aromatic hydrocarbons (1.21%) and pyrozole derivative (1.21%). However, among the monoterpene alcohol, the 1-phenylethyl alcohol (13.02%); citronellol (10.01%) and 6-octen-1-ol, 3,7-dimethyl (9.55%) were found in most abundant. Formulated hand sanitizer with REO exhibited physical and microbiological properties that were comparable with the market product. It also had pleasant scent, compatible with skin, easy to apply, and are acceptable to the users. The current study clearly shows that REO could be utilized as a potential ingredient in hand sanitizer formulation for giving the pleasant smell, acceptable physical and microbial quality parameters.